A Narrative Inquiry into the Roles of Debate in Developing an Indonesian EFL Teacher’s English Language Proficiency - Arief Eko Priyo Atmojo (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This narrative inquiry delves into how debate plays critical roles in developing an Indonesian EFL teacher’s English language proficiency. One female EFL teacher was purposefully recruited as the participant. Data were obtained through written reflections and semi-structured interviews. An inductive thematic analysis was then employed to analyze the data. The findings suggest that debate plays critical roles in promoting target language exposure, facilitating target language use, and becoming a conducive language learning environment, ultimately advancing English language proficiency. Debate is perceived to enhance vocabulary, rhetoric, and four main language skills: reading, writing, speaking, and listening. In addition to developing language proficiency, debate promotes essential academic skills, including arguing, public speaking, and critical thinking. Despite its advantages, encountered challenges can still be overcome. These findings highlight the transformative potentials of debate as a pedagogical strategy, underscoring its capacity to enhance language and academic skills. However, due to its limited generalizability, future studies should employ potential research designs and recruit diverse participants across various settings.